2020
DOI: 10.48550/arxiv.2011.07294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pose-dependent weights and Domain Randomization for fully automatic X-ray to CT Registration

Abstract: Fully automatic X-ray to CT registration requires a solid initialization to provide an initial alignment within the capture range of existing intensity-based registrations. This work adresses that need by providing a novel automatic initialization, which enables end to end registration. First, a neural network is trained once to detect a set of anatomical landmarks on simulated X-rays. A domain randomization scheme is proposed to enable the network to overcome the challenge of being trained purely on simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Use of simulated data in combination with domain randomization [3] or adversarial data augmentation [14] strategies can be explored to reduce the burden of annotated training data requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of simulated data in combination with domain randomization [3] or adversarial data augmentation [14] strategies can be explored to reduce the burden of annotated training data requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Deep Learning (DL) based techniques for 2D/3D registration problem have shown promising results, by improving the computational efficiency [11,17] and robustness [10,8,19]. Recent works have also shown that the robustness can be increased to a much greater extent using DL-based methods and even propose fully automatic 2D/3D registration solution [2,3]. However, most of these techniques rely on a final refinement step based on the classical methods to achieve the necessary registration accuracy for interventional application, which limits the computational efficiency of DL-based registration.…”
Section: Introductionmentioning
confidence: 99%